The spillover effects of military spending across superpowers using the TVP - VAR approach - Duc Hong Vo; Minh Phuoc Bao Tran; Phuong Thi Ha Cao (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
The amount of money spent on military activities across superpowers globally has generally caused significant concerns regarding military conflicts, the arms race, economic growth development, security, political stability, and governance. This paper investigates the spillover effects of military spending among the world’s largest spenders on military activities over the period 1997 - 2022. We use the advanced Time-Varying Parameter Vector Autoregressive (TVP-VAR) model to examine these effects, which is not used in the literature on defense economics. Our empirical results indicate the dynamic international spillovers of military spending among eleven countries. We find that the average total dynamic military spending connectedness was at the strongly interrelated level of 83.84 percent, ranging from 89.37 percent to 94.23 percent. Among these eleven, the world's largest spenders on military activities, the USA (China) is the most significant contributor (receiver) of total spillover. At the same time, Australia and Iran transmitted and received the least spillover of military spending.